IT`S SHOW TIME: VIOLÊNCIA E EMOÇÕES NO MIXED MARTIAL ARTS (MMA 1995 – 2016) - Carmo, Gonçalo Cassins Moreira do (2016)
This study, whose study problem is the relationship that is established between the violence and the emotion in the MMA, from the perspective of fighters and spectators,aims to analyze the violence and the emotion in the MMA from the perspective of both.Among the specific objectives are: historicizing the MMA; to present theoretical elements that allow the understanding of violence and emotion in the universe of MMA;to Identify what kind of emotion is present during the preparation period and the moment of the fight. The literature chosen to discuss the issue suggests that violence control has a strong association with emotional control (ELIAS; DUNNING, 1992).From the perspective of the fighters and spectators, is tried to discuss violence and emotion, using the concepts of symbolic violence, real violence, legitimate violence and systemic violence. From this, three hypothesis are presented: the first is that the MMA is a violent sport, conceived in this way in order to serve the demands of a society and a violent man by nature; The second one points out that the perception of fighters that the MMA is not violent is related to the fact that the competitions possess rules, unlike what happens on the streets. The third hypothesis upholds that there is a social need for the public to experience violence, which can be seen by the increasing demand for events involving MMA, indicated by the increase in TV ratings and the purchasing of pay-per-view packages. The proposed temporal frame refers to the period between 1995 and 2016. The initial time mark was established due to changes in the rules occurred after the UFC-5 event took place, a period in which the confrontations had no time limit, it means, there was no division by rounds, nor amaximum period length for the fight to end. After the changes, the fights began to occur with pre-established time length. Regarding the final temporal beacon, the year 2016, it is due to the edition of the UFC-198, held in the city of Curitiba-PR. In this event,spectators were interviewed, as well as, were concluded the semi-structured observations and interviews with the fighters. The methodology used was qualitative of the ethnographic type, whose instruments were the participating observation and semi-structured interviews. It was found that, from the perspective of fighters and spectators, the MMA is not a violent sport, although the literature and the interviews conducted with them show the presence of a symbolic violence during training and the moment of the combat. There is also a strong emotional appeal, in which happiness and fear are present. The text is structured in three chapters, by which it was sought to discuss violence and emotion based on the proposed theoretical framework and the performed interviews.